C1N1 Thin Films from Guanine Decomposition Fragments - Jerigova, Maria; Heske, Julian; Kühne, Thomas D.; Tian, Zhihong; Tovar, Michael; Odziomek, Mateusz; Lopez-Salas, Nieves (Advanced Materials Interfaces, 2023)
Polymeric semiconductors are finding a wide range of applications. In particular, graphitic carbon nitride g-C3N4 has been investigated extensively in the past decade. However, the family of carbon nitrides is not limited to C3N4 and new CXNY are now being explored due to their different bandgap energy, morphology, and overall physicochemical properties. Here, homogenous and semi-transparent C1N1 thin films are fabricated using guanine as a nontoxic molecular precursor. They are synthesized in a simplified chemical vapor deposition process on top of fused silica and fluorine doped tin oxide coated glass substrates. The chemical and structural studies reveal that C/N ratio is close to target 1, triazine vibrations are visible in vibrational spectra and stacking of the film is observed from glancing incidence X-ray diffraction data. The (photo)electrochemical properties are studied, the film is a p-type semiconductor with a good photoresponse to visible light and a suitable catalyst for hydrogen evolution reaction. A simple and safe way of synthesizing C1N1 films on a range of substrates is presented here.
CRIS-Team Scopus Importer:2023-03-20
Keywords: C; photoelectrochemistry; thin films